Mitochondrial Genetics and Human Health: Implications and Insights - HAMZA ALI; ABRAR AHMED RATTAR; MAHAM TAQI; RAFAY SHAIKH; ANOSH GILL (Pakistan Journal of Medical & Health Sciences, 2024)
Mitochondrial genetics is a crucial area of research with major implications for human health. Mitochondria are cellular organelles essential for energy production but also play vital roles in other cellular processes like calcium regulation and redox balance. Certain unique characteristics of the mitochondrial DNA (mt-DNA) including its high mutation rate, maternal inheritance and heteroplasmy make it central to understanding the wide range of genetic and complex diseases. This review examines the bridge between mt-DNA mutations and various diseases such as mitochondrial myopathies, neurodegenerative disorders and complex diseases like type 2 diabetes and cardiovascular disorders. Mutations in the mt-DNA lead to generation of reactive oxygen species (ROS) which leads to cellular damage and disease progression. The review explores different epigenetic factors such as environment. Lifestyle, aging impact the mitochondrial function with focus on the susceptibility of mt-DNA to oxidative damage due to its proximity to ROS generation sites The review also highlights the importance of mitochondrial genetics in reproductive health and provides insights on maternal transfer of mt-DNA and inherited mitochondrial disorders. These findings offer foundation for advancement in diagnosing, treating and preventing mitochondrial diseases, ultimately increasing our understanding of human biology and disease mechanism. Keywords: Mitochondrial genetics, Mitochondrial DNA (mt-DNA,) Mitochondria Genetic diseases, Mitochondrial myopathies, Neurodegenerative disorders, Type 2 diabetes, Cardiovascular disorder